Perceived Organizational Purpose: Systematic Literature Review, Construct Definition, Measurement and Potential Employee Outcomes - Jasinenko, Anna; Steuber, Josephina (Journal of Management Studies, 2023)
AbstractOrganizational purpose has recently gained great popularity in research and practice. However, the development of this nascent research field has struggled with definitional ambiguity, the lack of a measurement instrument and little empirical testing of potential outcomes. In our paper, we first introduce and define the multidimensional construct of perceived organizational purpose, which sheds light on the individual and subjective experiences of organizational purpose. Second, building on our construct definition, we develop and validate a four‐dimensional Perceived Organizational Purpose Scale. Third, we disentangle the related yet differentiated concepts of perceived organizational purpose and meaningful work and theorize how substantial knowledge in the field of meaningful work can be transferred to the relatively new and untested field of perceived organizational purpose. Fourth, we critically elaborate and empirically test the relationship of perceived organizational purpose with employee job satisfaction, subjective wellbeing and work‐life conflict.